(untitled) (gjstudies, 2021)
The regulatory landscape for audit firms has undergone significant transformation in recent decades, with enforcement actions serving as critical mechanismsfor maintaining market integrity and professional standards. While substantial research exists on the financial consequences of regulatory interventions, there remains a significant gap in understanding how these enforcement actions influence audit firm behavior through reputation channels and market signalingeffects. This research addresses this gap by examining the multifaceted relationship between regulatory enforcement and its subsequent impact on both targeted firms and the broader audit market ecosystem